When Women Rise, We All Rise: American Geriatrics Society Position Statement on Achieving Gender Equity in Geriatrics. Issue 12 (1st October 2019) - Boxer, Rebecca; Norman, Mary; Abadir, Peter; Beizer, Judith L.; Dierich, Mary; Lau, Samantha; Linnebur, Sunny A.; Lundebjerg, Nancy E.; Naik, Aanand D.; Schreiber, Robert; Unroe, Kathleen; Mikhailovich, Anna L.; et al.
Abstract : Supporting gender equity for women working in geriatrics is important to the growth of geriatrics across disciplines and is critical in achieving our vision for a future in which we are all able to contribute to our communities and maintain our health, safety, and independence as we age. Discrimination can have a negative impact on public health, particularly with regard to those who care for the health of older Americans and other vulnerable older people. Women working in the field of geriatrics have experienced implicit and explicit discriminatory practices that mirror available data on the entire workforce. In this position article, we outline strategic objectives and accompanying practical recommendations for how geriatrics, as a field, can work together to achieve a future in which the rights of women are guaranteed and women in geriatrics have the opportunity to achieve their full potential. This article represents the official positions of the American Geriatrics Society. J Am Geriatr Soc 67:2447–2454, 2019